Al-'Aql wa 'Alaqatuhu bi al-Din inda Thoha Abdurrahman - Ahmad Farid Saifuddin; Boma Panji Astha Tulung (University of Darussalam Gontor, Indonesia, 2021)
Islam considers the reason has a noble position in religion. Reason is man's tool of achieving knowledge, sometimes even the reason becomes the source of knowledge, both religious or general science. In the development of the world of Islamic thought, the issue of reason and its relationship with religion is still a relevant issue to be discussed up to now. The problems between reason and religion are the first, in Islam, there are some people or groups who are excessive in using one of them, and the second, in the West people are more inclined to do a dichotomy between knowledge that comes from reason and knowledge that comes from religion, even refused one of them. In this case, Taha Abdurrahman with his theory of reason and its relationship in religion tries to put the reason in its proper place and function, because according to Taha reason reaches perfection in his actions when the mind interacts with religious teachings because the reason and religion has characteristics at-ta'wan wa at-ta'dhud bainahima. By using a descriptive-analytical approach, this journal intends to discuss and research reason and its relation with religion according to Taha Abdurrahman.